The benefits of agroforestry - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
SOIL EROSION At ICRAF's research station in Kenya's semi arid zone, low hedgerows of Cassia siamea, a leguminous shrub from Asia, planted on the contours have led to the natural formation of micro-terraces on land sloping at 14%. The hedges take up...